Ginger and its active compounds in cancer therapy: From folk uses to nano-therapeutic applications. (February 2021) - Mahomoodally, M.F.; Aumeeruddy, M.Z.; Rengasamy, Kannan R.R.; Roshan, S.; Hammad, S.; Pandohee, J.; Hu, Xuebo; Zengin, G.
Graphical abstract: Abstract: Ginger is a spice that is renowned for its characteristic aromatic fragrance and pungent taste, with documented healing properties. Field studies conducted in several Asian and African countries revealed that ginger is used traditionally in the management of cancer. The scientific community has probed into the biological validation of its extracts and isolated compounds including the gingerols, shogaols, zingiberene, and zingerone, through in-vitro and in-vivo studies. Nonetheless, an updated compilation of these data together with a deep mechanistic approach is yet to be provided. Accordingly, this review highlights the mechanisms and therapeutics of ginger and its bioactive compounds focused on a cancer context and these evidence are based on the (i) cytotoxic effect against cancer cell lines, (ii) enzyme inhibitory action, (iii) combination therapy with chemotherapeutic and phenolic compounds, (iv) possible links to the microbiome and (v) the use of nano-formulations of ginger bioactive compounds as a more effective drug delivery strategy in cancer therapy.